Involvement of the superoxide dismutase enzyme in the mycorrhization process - Arines, Justo; Vilarino, Antonio; Palma, José M. (Agricultural Research Centre of Finland, 1994)
Mykorritsan avulla voidaan lisätä mikrolisättyjen kasvien eloonjäämistä ja parantaa kasvien laatua. Tiedetään, että mykorritsa auttaa merkittävästi kasveja vaikeissa olosuhteissa. Tämän ilmiön mekanismia ei täysin tunneta, mutta kasvien stressiä lievittävillä entsyymeillä näyttää olevan siinä tärkeä merkitys. Tästä syystä tutkimme superoksididismutaasientsyymejä (SOD; EC 1.15.1.1). Superoksidiradikaalien (SOR) syntymistä ja SOD-isotsyymien merkitystä detoksifikaatiossa selvitettiin myös yksityiskohtaisesti. Myös esimerkkejä näiden entsyymien ilmenemisen muuttumisesta symbioottisissa tapahtumissa on annettu.

The survivability and quality of micropropagated plants can be improved through mycorrhization. We consider that mycorrhization is important in supporting plants under stress conditions. The mechanism is not fully understood, but it seems that the enzymes involved in alleviating stress are important factors. We therefore studied superoxide dismutase (SOD; EC 1.15.1.1) isozymes. Insight is provided into the generation of superoxide radicals (SORs) and the detoxification role of SOD isozymes. Examples of how the expression of this enzyme changes in symbiotic processes are also given.
Keywords: Pu; mikrolisäys; mykorritsa; activated oxygen species; arbuscular mycorrhizal fungi; isozymes; oxidative stress; pathogenesis; superoxide radical